Value-added analysis of tuna fish floss: A case study of IKM Raja Bawang in supporting food security - Rasyid, Sofya A. (Jurnal Bisnis Kehutanan dan Lingkungan, 2025)
Background: Agroindustry is one of the strategic solutions in the development of fishery products, as it not only increases fishery yields but also contributes to improving income and strengthening the regional economy. Additionally, processing fish into value-added products, such as shredded tuna, can support food security through the diversification of processed products with longer shelf life and preserved nutritional value. This study aims to analyze the added value of processing tuna into shredded fish and its contribution to food security. Method: The research location was determined puIDRosive, based on the consideration that Raja Bawang IKM is one of the growing agro-industrial businesses producing shredded tuna in Palu City. Respondents were also selected puIDRosively through direct interviews with 1 leader/owner of Raja Bawang IKM, 1 deputy leader, and 4 employees. Thus, the total number of respondents was 6 people who had the competence to provide information related to the business and production of shredded fish. The data used in this study include both primary and secondary data. Value-added analysis was conducted using the Hayami method to determine output value, added value, profit, and labor contribution. Findings: The results show that the processing of tuna into shredded fish at Raja Bawang IKM generates an added value of IDR 40,163/kg with an added value ratio of 37.61%. The resulting profit reached IDR 16,163/kg with a profit rate of 40.24%. Conclusion: The findings indicate that processing tuna into shredded tuna not only provides economic benefits to business actors but also supports food security by supplying processed fish products with high nutritional value and longer shelf life. Novelty/Originality of This Article: It highlights the dual impact of value-added processing in enhancing business profitability and supporting local food security—an area that has received limited attention in prior studies, particularly in the context of micro-scale industries.